A Look at Kandara Qal, upstream from Qasr Shemamok(*) (Iraqi Kurdistan) - Dolce, Rita (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2020)
The archaeological project comprising the first eight excavation campaigns conducted at the site of Qasr Shemamok (henceforth QS) and directed by M. Masetti and O. Rouault focused in the first instance on bringing to light the historical and cultural phases of the ancient Kilizu between the Late Bronze Period and the Iron Age; and, secondly, at defining the earlier occupations at the site and in the surrounding area with a view to reconstructing its settlement history and urban characteristics during the Early Bronze Period.